Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1021/jp110741y
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Ultrafast Photophysics of Oxidized and Reduced FAD in Solution

Abstract: The ultrafast photophysics of oxidized and reduced flavin adenine dinucleotide (FAD) in aqueous solution was studied by broadband UV-vis femtosecond transient absorption spectroscopy. We observed that oxidized FAD (FAD(ox)) in solution readily aggregates at submillimolar concentration. Upon excitation of FAD(ox), three excited-state lifetimes were found and assigned to three different species: the closed (stacked) conformation of the monomer (∼5.4 ps), the open (extended) conformation of the monomer (∼2.8 ns),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
51
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(70 citation statements)
references
References 60 publications
18
51
0
Order By: Relevance
“…S2, and they show a highly multiphasic fluorescence decay, spanning timescales from ∼1 ps to ∼1 ns. However, all decay occurs substantially faster than the intrinsic nanosecond (∼3 ns) decay of FAD (23). The most probable origin of this quenching is electron transfer (ET) from close-by aromatic residues to the excited flavin cofactor.…”
Section: Resultsmentioning
confidence: 99%
“…S2, and they show a highly multiphasic fluorescence decay, spanning timescales from ∼1 ps to ∼1 ns. However, all decay occurs substantially faster than the intrinsic nanosecond (∼3 ns) decay of FAD (23). The most probable origin of this quenching is electron transfer (ET) from close-by aromatic residues to the excited flavin cofactor.…”
Section: Resultsmentioning
confidence: 99%
“…These are characteristic features of excited FAD ox (FAD ox *), already observed in other photolyases or cryptochrome, 25,27,28 different flavoproteins, 42,43 as well as for free FAD ox in solution. 41,44 The evolution of the transient absorption spectra may be divided into three phases, as follows:…”
Section: Spectral Analysismentioning
confidence: 99%
“…In addition, EADS1', as EADS1, is highly characteristic of a bound flavin, its SE band being in particular considerably more blue shifted than that of free FAD. 44 Currently, one may hypothesize the presence of a minority population of MmCPDII that exhibits a larger distance between FAD and the proximal tryptophan. Note that multiexponential FAD ox * decays have repeatedly been observed in BLUF proteins, caused by a FAD-tyrosine electron transfer, and explained in a similar way.…”
Section: Difference Between Eads2 and Eads3mentioning
confidence: 99%
“…It has been demonstrated that FAD in solution can exist in two different conformations [8,9]: open (fluorescent) and stacked (non-fluorescent). Depending on the environment of a particular enzyme, one of these conformations will predominate.…”
Section: -Introductionmentioning
confidence: 99%